Evaluación del Consumo de Agua Potable en Barrios/Domicilios de la Ciudad de Encarnación, Generación de Históricos y Concienciación e Instalación de Micro Medidores (Journal on studies and research of academic knowledge, 2016)
People superficially know the effects of indiscriminate drinking water but are totally unaware of what a stopcock badly closed, a broken toilet water tank or a broken pipe means for the delicate supply system, even more for the future of our precious resource (water) and the costs that each liter imply to have at home. This study aims to demonstrate how important the measurement by dial water meter in private homes because the low cost for the use of drinking water generates a critical awareness. The statistical work together with consumer information and measurement verified and analyzed the effect. It is only with technology and research that it can be understood through traditional user's behavior and their daily consumption. The main objective data from the area was obtained in our area per capita consumption. The specific objectives were decisive as they extended the study on the right path and allowed to learn about unknown information. The results are worrying. indiscriminate consumption is a fact and only the installation of dial water meter per user can regulate their consumption to the optimum value without wasting water.
Keywords: potable water; consumption per capita; awareness; dial water meter